2020
DOI: 10.14309/ctg.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intermittent Colonic Exoperistalsis Device to Treat Chronic Constipation: A Prospective Multicentric Clinical Trial

Abstract: INTRODUCTION: Chronic constipation is associated with various comorbidities and reduced quality of life. Current solutions, either pharmacological or invasive, show limited efficacy. Manual colon-specific massage is a well-established intervention to treat chronic constipation, but it should be applied daily. MOWOOT automatically provides intermittent colonic exo-peristalsis (ICE) treatment like that in manual massage. METHODS: This study assessed the safety and effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Enterosgel, an intestinal adsorbent approved for use in IBS-D and available over-the-counter in the UK is currently the subject of a multicentre RCT in IBS-D. 295 For IBS-C, there are ongoing trials of an exo-peristalsis device. 296 Future research priorities are outlined below.…”
Section: Other Treatments In Developmentmentioning
confidence: 99%
“…Enterosgel, an intestinal adsorbent approved for use in IBS-D and available over-the-counter in the UK is currently the subject of a multicentre RCT in IBS-D. 295 For IBS-C, there are ongoing trials of an exo-peristalsis device. 296 Future research priorities are outlined below.…”
Section: Other Treatments In Developmentmentioning
confidence: 99%
“…A recent clinical trial has reported the benefits of ICE treatment in patients with chronic constipation [ 13 ]. This trial showed reduced symptoms of discomfort and reduced use of evacuation aids, demonstrating the efficacy of a four-week intervention.…”
Section: Discussionmentioning
confidence: 99%
“…MOWOOT is an automated intermittent colonic exoperistalsis (ICE) treatment device simulating the natural peristaltic contractions of the colon. In a multicentric clinical trial, the ICE device has shown safety and efficacy in patients with chronic constipation due to several causes, reducing constipation symptoms and evacuation aids, with a concomitant increase in the number of complete bowel movements and excellent adherence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This stimulation crosses two medium-frequency, out-of-phase currents from anterior and posterior abdominal locations to cross-sect to create a new modulated, low-frequency, intra-abdominal current, not generated by traditional TENS. Intermittent colonic exoperistalsis (ICE), a pneumatic abdominal massaging belt with four actuators providing rotating pressure, demonstrated improvement in CSBMs, reduced constipation symptoms, and decreased laxative use after 20-min daily sessions over 4 weeks in an open-label study of patients with neurogenic bowel and constipation [35].…”
Section: Nonpharmacological Treatmentsmentioning
confidence: 99%